The effect of fashion trends and perceived quality on Gen Z purchase decisions: Evidence from Bloods product in Garut - Rizky Rahayu Putra; Rohimat Nurhasan; Dioka Muhamad (Nur Science Institute, 2026)
This study examines the influence of fashion trends and perceived quality on Generation Z consumers’ purchase decisions for Bloods products in Garut, Indonesia. Using an explanatory quantitative design, data were collected from Generation Z respondents through purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS to test the relationships among the proposed variables. The findings show that fashion trends do not significantly affect purchase decisions, whereas perceived quality has a positive and significant effect. These results indicate that, in this context, Generation Z consumers in Garut are more likely to consider product quality than fashion trend alignment when making purchase decisions. The findings also suggest that the appeal of Bloods products depends less on changing fashion trends and more on the brand’s ability to build a strong perception of quality. This study contributes to consumer behavior research in the context of local fashion brands and offers practical implications for businesses targeting Generation Z consumers through quality-oriented marketing strategies.